A comparative study of the effect of the soil constitutive model on the seismic response of buried concrete pipes - Alzabeebee, Saif (Journal of Pipeline Science and Engineering, 2022)
No attention has been given in previous studies to understand the influence of the sophistication of the soil constitutive model on the response of buried concrete pipes subjected to transverse seismic effect. This research, therefore, has been conducted to address this gap in knowledge by analyzing the behavior of a buried concrete pipe subjected to transverse seismic shake employing the linear elastic (LE) model, elasto-plastic Mohr-Coulomb (MC) model, hardening soil (Hs) model, and hardening soil model with small strain stiffness (Hs small) to provide a benchmark study that helps the designers and the researchers to select the most suitable and less computationally demanding soil constitutive model. The cases of good and poor installation conditions have been considered in the analyses. In addition, numerous earthquake records have been used to allow the consideration of wide range of earthquake intensities to aid general conclusions. It was found that all of the considered constitutive models produce the same trend of the circumferential bending moment (BM) that is developed around the pipe. In general, the maximum BM produced using the LE and MC models is significantly lower than that produced using the Hs and Hs small models with one exception for the LE model for a predominant frequency of 0.66 Hz. Furthermore, the maximum BM produced using the LE and MC models is not sensitive to the increase of the peak ground acceleration (PGA). More importantly, the Hs and Hs small models produce almost similar results with a percentage difference ranges between 1% to 9%. In addition, the Hs and Hs small models show a decrease of the maximum BM as the predominant frequency rises and an increase of the maximum BM as the PGA rises.